Bathers, bodies, beauty the visceral eye - Nochlin, Linda (Charles Eliot Norton lectures, 2006)
To the eye of some viewers, Renoir's Great Bathers are the very picture of female sensuality and beauty. To others, they embody a whole tradition of masculine mastery and feminine display. Yet others find in the bathers a feminine fantasy of bodily liberation. The points of view are many, various, occasionally startling--and through them, Linda Nochlin explores the contradictions and dissonances that mark experience as well as art. Her book--about art, the body, beauty, and ways of viewing--confronts the issues posed in representations particularly of the female body in the art of impressionists, modern masters, and contemporary realists and post-modernists. Nochlin begins by focusing on the painterly preoccupation with bathing, whether at the beach, in lakes and rivers, in public swimming pools, or in bathtubs. In discussions of Renoir, Manet, Cezanne, Bonnard, and Picasso, of late-twentieth-century and contemporary artists such as Philip Pearlstein, Alice Neel, and Jenny Saville, of grotesque imagery, the concept of beauty, and the body in realism, she develops an interpretive collage incorporating the readings of differing, strong-willed, female viewpoints. Among these is, of course, Nochlin's own, a vantage point subtly charted here through a longtime engagement with art, art history, and artists. In many ways a personal book, Bathers, Bodies, Beauty brings to bear a lifetime of looking at, teaching, talking about, wrestling with, loving, and hating art to reveal and complicate the lived and felt--the visceral--experience of art.